Pengaruh Model Pembelajaran Kooperatif Tipe Think-Pair-Share Terhadap Kemampuan Komunikasi Matematis Siswa SMA Swasta Markus Medan - Martogi Ray Martin Situmorang; Yasifati Hia (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine whether there is an influence of the think pair share cooperative learning model on students' mathematical communication skills. This research was conducted at SMA Markus Medan. The research method used is a quasi experimental method. The sample in this study consisted of two classes, namely class XI IPA-1 as the experimental class and class XI IPA-2 as the control class. The experimental class uses the think pair share learning model, and the control class uses conventional learning. The average result of the final test score (post-test) for experimental class students was 84.33, while in the control class the average final test score for students was 70.14. In the hypothesis test, the results of the mean difference test (t-test) were obtained with the statistical value > (8,342 > 1,671), which means that there is an influence from the use of the think pair share learning model applied in the experimental class. This indicates that the mathematical communication skills of experimental class students are better than those in the control class.